Evaluating Knowledge of Autonomic Dysreflexia Among Individuals With Spinal Cord Injury and Their Families - McGillivray, Colleen F (American Paraplegia Society, 2009)
BACKGROUND/OBJECTIVE: Autonomic dysreflexia (AD) is a potentially life-threatening complication of spinal cord injury (SCI) characterized by episodic paroxysmal hypertension and bradycardia in response to a noxious stimulus below the level of injury. Recognition of AD is crucial for individuals with SCI and their family members to facilitate timely and appropriate management. The objectives of this study were to (a) evaluate knowledge of AD among SCI consumers and their family members and (b) identify the preferred format and timing of education regarding AD recognition and management for these stakeholders. METHODS: Cross-sectional descriptive study on a cohort of community-dwelling individuals with chronic SCI (N = 100) and their family members (N = 16) by self-report mail survey. Frequency distributions were used to tabulate survey responses on AD knowledge level and to characterize learning preferences and 2 × 2 χ(2) analyses were conducted to determine whether there were factors (ie, impairment) associated with AD knowledge (ie, how to treat AD). RESULTS: Individuals with SCI and their family members have gaps in their knowledge of AD. Traumatic SCI etiology (vs nontrauma) was associated with greater knowledge about treating AD. Although the SCI sample was a high-risk group, 41% had not heard of AD. More concerning was that 22% of individuals with SCI reported symptoms consistent with unrecognized AD. Respondents indicated that AD education would be best delivered during rehabilitation by a healthcare professional. CONCLUSIONS: Further work is needed to promote knowledge about recognizing and managing AD. This may help reduce risk of cardiac and cerebrovascular disease in the SCI population.